Evidence of Criterion Validity of BILOv3 in Children in Southern Brazil - Reppold, Caroline Tozzi (2015)
To diagnose possible difficulties and intervene it is essential to preemptively evaluate the performance ofchildren in oral language comprehension. In context, the present study aimed to look for evidences of criterion validity in the“Bateria Informatizada de Linguagem Oral (BILOv3)”,considering age, sex and level of education. 474 children between 6and 11 years old, from the 5th grade of middle school from 10 schools from Rio Grande do Sul, took part in the study. TheBILOv3 was administrated collectively and each child used a computer. Application of the instrument took approximately 35minutes. Statistically significant differences were found for sex in the “Completar Histórias (CH)” and “Interpretar Histórias(IH)” tests, for age in the “Completar Frases (CF)” and “Completar Histórias (CH)” tests and for level of education in theCF, CH and IH tests. The BILOv3 is sensitive to capture differences between sex, school grade and age of students and,therefore, shows evidence of criterion validity. This suggests the possibility of clinical use and use in schools, aiming at earlyidentification of language difficulties.